DAMPAK SUPERVISI KEPALA SEKOLAH TERHADAP KINERJA GURU DI TINGKAT SEKOLAH LANJUTAN TINGKAT PERTAMA (SLTP) - Ibnu Syaakir; Donal Devi Amdanata (Indragiri Research Center (ingreat), 2023)
This study aims to analyze the impact of school principals' supervision on teacher performance in public Junior High Schools (SLTP) in the Batang Tuaka District. School principals' supervision is an essential factor in improving teaching quality, teacher motivation, and collaboration among teachers. Descriptive research method was employed, gathering data through observations, interviews, and documentary studies. The results of the study indicate that school principals' supervision has a positive impact on teacher performance. Directed and effective supervision helps improve the quality of teachers' instruction, motivates teachers in carrying out their duties, and fosters collaboration among teachers. Supporting factors such as effective communication, active teacher involvement, consistent support from school principals, and a school culture that supports the professional development of teachers also play a vital role in maximizing the impact of school principals' supervision. Therefore, it is recommended that school principals and relevant stakeholders pay serious attention to the practice of school principals' supervision to enhance the quality of education in public Junior High Schools in the Batang Tuaka District. This study provides a significant contribution to understanding the relationship between school principals' supervision and teacher performance in the context of public Junior High Schools.